2000
DOI: 10.1093/emboj/19.10.2152
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the bacteriorhodopsin mutant F219L N intermediate revealed by electron crystallography

Abstract: Bacteriorhodopsin is a light‐driven proton pump in halobacteria that forms crystalline patches in the cell membrane. Isomerization of the bound retinal initiates a photocycle resulting in the extrusion of a proton. An electron crystallographic analysis of the N intermediate from the mutant F219L gives a three‐dimensional view of the large conformational change that occurs on the cytoplasmic side after deprotonation of the retinal Schiff base. Helix F, together with helix E, tilts away from the center of the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
110
1
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(121 citation statements)
references
References 60 publications
9
110
1
1
Order By: Relevance
“…The atomic resolution structure of the D96N MN intermediate, which is an N intermediate-like structure, was revealed, but its cytoplasmic side of the F and G helices could not be modeled because of disordering by the movement of these regions (24). This may be explained by movement of the F helix toward neighbors in the crystal lattice being too large to allow all molecules to change conformation simultaneously (23). All these results agree with our results and indicate that the cytoplasmic end of the F helix moves outward extensively in the M-N transition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The atomic resolution structure of the D96N MN intermediate, which is an N intermediate-like structure, was revealed, but its cytoplasmic side of the F and G helices could not be modeled because of disordering by the movement of these regions (24). This may be explained by movement of the F helix toward neighbors in the crystal lattice being too large to allow all molecules to change conformation simultaneously (23). All these results agree with our results and indicate that the cytoplasmic end of the F helix moves outward extensively in the M-N transition.…”
Section: Discussionmentioning
confidence: 99%
“…Thorgeirsson et al (22) clearly showed that the EF loop moves in the M-N transition. The result of an electron diffraction experiment also showed that the cytoplasmic end of the F helix is open in the N intermediate (23). The atomic resolution structure of the D96N MN intermediate, which is an N intermediate-like structure, was revealed, but its cytoplasmic side of the F and G helices could not be modeled because of disordering by the movement of these regions (24).…”
Section: Discussionmentioning
confidence: 99%
“…In general, at low temperatures the thermal motions that aid the crossing of energy barriers associated with specific transitions can be reduced or even frozen out, and light activation of three-dimensional crystals can populate specific photocycle intermediates (5)(6)(7)(8)(9). Using this approach, a number of x-ray and electron diffraction studies on light-driven structural changes in bR (1, 10 -16) and in bR mutants (17)(18)(19), as well as bR mutant intermediate state analogues (20,21), have been presented recently. When taken together with an acceptance of the limitations of the techniques of kinetic crystallography, most structures combine to yield a remarkably consistent picture of the structural mechanism of outwardly directed proton pumping by bR (22).…”
Section: Bacteriorhodopsin (Br)mentioning
confidence: 99%
“…However, a larger structural change in bR was reported in 3 the electron crystallography study of the D96G, F171C, F219L triple mutant of bR: displacement of helix F by ~0.35 nm away from the center of the protein 23 . The electron crystallography study of the F219L mutant further reported that helices E and F tilt away from the center of the protein, which is followed by a shift of the E-F loop by ~0.3 nm 24 , resulting in large-scale conformational changes in the M and N states 18,19,25 .…”
mentioning
confidence: 99%
“…In the photocycle, a series of spectral intermediates, designated J, K, L, M, N, and O, occur in that order 12 . The light-induced conformational changes in bR have been investigated by various methods [15][16][17][18][19][20][21][22][23][24][25] , leading to a consensus that the proton channel at the cytoplasmic surface is opened by the tilting of helix F away from the protein center 21,23,24 . Sass et al reported helix F displacement of ~0.1 nm in the late M state, based on X-ray diffraction of the three-dimensional crystal of wild type (WT) 21 .…”
mentioning
confidence: 99%